Status of Corporate Social Responsibility in Commercial Bank of Nepal with reference to Prabhu Bank Limited - Dwibedi, Lalan (Academic Voices: A Multidisciplinary Journal, 2020)
The purpose of the study is to assess the status and practices of CSR and to find out whether the commercial banks perform the CSR activities as per their capability or not by investigating why companies engage in CSR and how CSR can affect financial performance and employee motivation. This study follows exploratory and descriptive research design. Primary data are collected through the structured questionnaires. Prabhu bank Ltd is taken as the case study out of total commercial bank. It was found that all the respondents were very positive and energized by the CSR activities provided by the Bank. Majority of the respondents’ views that CSR activities has the positive relationship with employee motivation and could positively contribute to the financial performance of the company as it increases the good image and goodwill of the organization. Education program, health facilities and environment protection activities are taken as important desired CSR factor by the respondents. In Nepalese context the organization should shifted their priorities from earning more profit to give priorities to CSR activities and flourish their business.